Changes E3 ubiquitin protein ligase 1 gene mRNA expression correlated with IgA1 glycosylation in patients with IgA nephropathy. (1st January 2019) - Liu, Youxia; Zheng, Jie; Jia, Junya; Li, Hongfen; Hu, Shuiyi; Lin, Yujia; Yan, Tiekun
Abstract: Background: Recent genomewide association study suggested that the top single-nucleotide polymorphism, rs978056, in HECW1 gene (which encodes HECT, C2 and WW domain containing E3 ubiquitin protein ligase 1) associated with the levels of galactose-deficient IgA1 (Gd-IgA1) in IgA nephropathy (IgAN). However, HECW1 expression in IgAN has not yet been examined. Methods: In the following study, we have enrolled 40 patients with IgAN and 40 healthy controls. The expression level of HECW1, as well as plasma levels of Gd-IgA1 and IgA1, were determined detected. Results: IgAN patients presented with significantly elevated Gd-IgA1 and IgA1 levels compared with those of the healthy controls ( p  < .001 and p  = .03, respectively). We further divided the patients into two groups according to the median level of HECW1 (0.58). We found the levels of Gd-IgA1 and IgA1 were significantly higher in low HECW1 level group compared with those in high HECW1 level group ( p  = .02 and p  = .04, respectively). And HECW1 mRNA expression had a significant inverse correlation with Gd-IgA1 levels in IgAN patients ( r = −0.34, p  = .03). It seemed that the risk genotype (rs978056 GG) was associated with reduced HECW1 expression in 80 Han Chinese from Beijing, although the difference was not significant ( p  = .09). No significant association with clinical and pathological manifestations was observed between patients with high and low levels of HECW1. Conclusion: We reported for the first time that HECW1 mRNA levels were negatively correlated with Gd-IgA1 levels. Our study points to a new regulatory mechanism of IgAN that can explain the aberrant glycosylation of IgA1.